Apixaban (I) in several aqueous co-solvent mixtures: Solubility, solvent effect and preferential solvation. (November 2020) - Li, Huanxin; Farajtabar, Ali; Xie, Yingnan; Li, Zhaoyan; Zhao, Hongkun
Graphic abstract: Highlights: Apixaban (I) solubility in four aqueous co-solvent mixtures was determined. Solubility data was correlated Jouyban-Acree and van't Hoff-Jouyban-Acree models. Preferential solvation of apixaban (I) in four mixtures was studied via IKBI technique. Solvent effect was studied in terms of solute-solvent and solvent-solvent interactions. Abstract: Equilibrium apixaban (I) solubility in isopropanol (1) + water (2), ethanol (1) + water (2), acetone (1) + water (2) and methanol (1) + water (2) mixtures was acquired by a shake-flask method from 288.15 K to 328.15 K under atmospheric pressure of 101.2 kPa. At a certain temperature, the highest apixaban (I) solubility in mole fraction scale was observed in neat solvents of acetone/methanol for the acetone/methanol (1) + water (2) solutions; while for the ethanol/isopropanol (1) + water (2) solutions, the solubility data presented a maximum value with the ethanol/isopropanol mass fraction of about 0.8. The determined solubility values were treated by linear solvation energy relationships in order to explain the solvent effect and find its major descriptors. The preferential solvation was studied by the method of inverse Kirkwood–Buff integrals based on some thermodynamic solution properties. In the methanol (1) + water (2) mixture with compositions 0.31 < x 1 < 1, ethanol (1) + water (2) mixture with compositions 0.25 < x 1 < 0.58, isopropanol (1) + water (2) mixture with compositions 0.25 < x 1 < 0.53, acetone (1) + water (2) mixture with compositions 0.20 < x 1 < 1 and 1, 4-dioxane (1) + water (2) mixture with compositions 0.175 < x 1 < 0.570, the preferential solvation parameters for methanol/ethanol/isopropanol/acetone/1, 4-dioxane were positive values, indicating that apixaban (I) was preferentially solvated by the co-solvents. It is conjecturable that in these regions apixaban (I) serves as a Lewis acid with the molecules of organic solvents. Moreover, the drug solubility was correlated through the Jouyban-Acree and van't Hoff-Jouyban-Acree models attaining average relative deviations less than 9.64%.